2016
DOI: 10.1515/rjim-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal Syndrome: Diagnosis and Treatment – newsreel –

Abstract: Hepatorenal syndrome (HRS) is defined as renal failure that occurs in the presence of severe acute or chronic liver disease in the absence of underlying renal pathology. Due to the functional nature of the disease and the absence of specific diagnostic markers, HRS diagnosis is determined based on positive criteria associated with excluding other causes of renal failure in patients with liver cirrhosis and ascites. Differentiation from other types of acute or chronic renal disease is extremely difficult and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…En ausencia de un marcador bioquímico o radiológico especí co, el diagnóstico del SHR se basa en criterios que excluyen otras causas de daño renal como: hipovolemia, la presencia de daño renal estructural (necrosis tubular aguda, glomerulonefritis y nefritis intersticial aguda) o daño renal obstructivo (uropatía obstructiva) [31][32][33]. Es necesario determinar si hay evidencia de infección sobre diuresis, hemorragia gastrointestinal, uso reciente de vasodilatadores o nefrotoxinas (incluidos medicamentos antiin amatorios no esteroideos) o paracentesis de gran volumen sin el uso de albúmina.…”
Section: Diagnósticounclassified
“…En ausencia de un marcador bioquímico o radiológico especí co, el diagnóstico del SHR se basa en criterios que excluyen otras causas de daño renal como: hipovolemia, la presencia de daño renal estructural (necrosis tubular aguda, glomerulonefritis y nefritis intersticial aguda) o daño renal obstructivo (uropatía obstructiva) [31][32][33]. Es necesario determinar si hay evidencia de infección sobre diuresis, hemorragia gastrointestinal, uso reciente de vasodilatadores o nefrotoxinas (incluidos medicamentos antiin amatorios no esteroideos) o paracentesis de gran volumen sin el uso de albúmina.…”
Section: Diagnósticounclassified
“…It has been shown that acute reductions in blood flow or increased hepatic resistance cause rapid stimulation of the SNS resulting in renal vasoconstriction and reduced kidney function with stimulation of the RAAS (Figure 2). 16,17 Liver cirrhosis is associated with a substantial release of glutamine into the portal vein, and that causes hepatocyte swelling and activates chemoreceptors that lead to more activation of the SNS. 17 The reflex nature of the response to low hepatic blood flow is supported by studies which show that denervation of the liver and/or kidney decreases SNS and improves renal blood flow and Na + excretion.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It is due to splanchnic vasodilation, which results in renal vasoconstriction with consequent reduction in renal plasma flow and glomerular filtration rate. 1 In the United States, treatment is with a combination of octreotide, midodrine, and human albumin to increase the effective blood volume and subsequently improve renal function. 2 While octreotide, a long-acting somatostatin analog, is used to induce splanchnic vasoconstriction in this setting, it also affects the secretion of insulin and glucagon.…”
Section: Introductionmentioning
confidence: 99%